Formal and Semantic Structure of Contexts of Text Clip AND THEN - E. S. Sheremetyeva; Xiaomin Cao (Научный диалог, 2022)
The textual clip AND THEN from the point of view of its formation as a service unit and from the point of view of the specifics of the contexts in which it functions is considered. The research material is taken from the National Corpus of the Russian Language. The relevance of the work is due to the fact that the object of study is of interest both in terms of a multidimensional study of the system of functional words in general and specialized means of text communication, in particular, and in the aspect of studying the principles of organizing the text itself, forming its content and structure. It is argued that the semantics of succession the elements that make up the clip AND THEN was the basis for the development of the textual function of the clip. The connective semantics of the clip is substantiated on the basis of its function of introducing an additional message and a marker for changing the aspect of the discussion of one topic. It is proved that the textual clip does not indicate the relationship of succession between propositions, but the sequence in the development of the speaker’s thought. Particular attention is paid to the classification of typical contexts of the clip, built considering the nature of the relationships within the text fragments connected with the clip. It is concluded that the textual clip AND THEN has both the ability to thematic organization of the text, and the signs of an indicator of logical-semantic relations.